Model Pembelajaran Debat Dalam Pembelajaran PKn SD Kelas VI - Imam Nawawi (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2010)
Abstract: Debat teaching modelin teaching Pancasila citizenship and education of sixth grade elementary schools’ students. Debat teaching model is an adaptation of open discussion models with debat conditions. The use of this model is appropriate for sixth grade elementary school students because in the implementation consistent to children’s thinking and development. The learning materials are selected and arranged into pro and contra, Students assigned become two groups. In their group, there are pro and contra groups which conduct debat about topic given. In this context, students are trained to elicitate their opinion/ thinking and to defend the opinion based on logical reasoning and it should be with responsibility. Students are not become enemy but they should learn  appreciate the difference. Reports of each groups (pro and con) give to teachers. Eventually, teachers evaluated every students about their material comprehension which includes both positions and evaluated effectiveness of students involvement in the debat.Abstrak : Pembelajaran model debat merupakan adaptasi dari model-model diskusi terbuka yang membawa pada suasana debat. Penggunaan model ini cocok digunakan di kelas 6 SD karena dalam hal penggunaan juga melihat pada tingkat perkembangan dan berpikir anak. Materi ajar dipilih dan disusun menjadi paket pro dan kontra. Siswa dibagi ke dalam dua kelompok. Di dalam kelompoknya, terdapat kubu/kelompok pro dan kontra yang melakukan perdebatan tentang topik yang ditugaskan. Dalam hal ini siswa dilatih untuk mengutarakan pendapat/pemikirannya dan bagaimana mempertahankan pendapatnya dengan alasan-alasan yang logis dan dapat dipertanggungjawabkan. Bukan berarti siswa diajak saling bermusuhan, melainkan siswa belajar tentang  menghargai adanya perbedaan. Laporan masing-masing kelompok yang menyangkut kedua posisi pro dan kontra diberikan kepada guru. Selanjutnya guru dapat mengevaluasi setiap siswa tentang penguasaan materi yang meliputi kedua posisi tersebut dan mengevaluasi seberapa efektif siswa terlibat dalam prosedur debat.